Effect of intravenous alteplase on ischaemic lesion water homeostasis. (18th October 2019) - Broocks, G.; Kniep, H.; Kemmling, A.; Flottmann, F.; Nawabi, J.; Elsayed, S.; Schön, G.; Thomalla, G.; Fiehler, J.; Hanning, U.
Abstract : Background and purpose: Intravenous (IV) lysis with alteplase is known to increase biomarkers of blood–brain barrier breakdown and has therefore been associated with secondary injuries such as hemorrhagic transformation. The impact of alteplase on brain edema formation, however, has not been investigated yet. The purpose was to examine the effects of IV alteplase on ischaemic lesion water homeostasis differentiated from final tissue infarct in patients with and without successful endovascular therapy (sET). Methods: In all, 232 middle cerebral artery stroke patients were analyzed. 147 patients received IV alteplase, of whom 106 patients received subsequent sET. Out of 85 patients without IV alteplase, 50 received sET. Ischaemic brain edema was quantified at admission and follow‐up computed tomography using quantitative lesion net water uptake (NWU) and its difference was calculated (ΔNWU). The relationship of alteplase on ΔNWU and edema‐corrected final infarct volume was analyzed using univariate and multivariate linear regression models. Results: The mean ΔNWU was 11.8% (SD 7.9) in patients with alteplase and 11.5% (SD 8.3) in patients without alteplase ( P = 0.8). Alteplase was not associated with lowered ΔNWU whilst being associated with reduced edema‐corrected tissue infarct volume [−27.4 ml, 95% confidence interval (CI) −49.4 to −5.4 ml; P = 0.02], adjusted for the Alberta Stroke Program Early Computed Tomography Score and recanalization status. In patients with sET, ΔNWU was 10.5% (95% CI 6.3%–10.5%) for patients with IV alteplase and 8.4% (95% CI 9.1%–12.0%) for patients without IV alteplase. Conclusion: The application of IV alteplase did not significantly alter ischaemic lesion water homeostasis but was associated with reduced edema‐corrected tissue infarct volume, which might be directly linked to improved functional outcome.